Innovation adaptation and post-entry growth in international new ventures - Encarnación Ramos-Hidalgo; Jude Ndubuisi Edeh; Francisco J. Acedo (European Research on Management and Business Economics (ERMBE), 2022)
Innovation plays a vital role in the internationalization process of international new ventures (INVs). However, to date, there are insufficient empirical studies exploring the innovation decisions that enable these firms to grow once the internationalization process has started. In response to this research gap, this paper examines the impacts of the technological pattern adopted at the initial foreign entry and the decisions to improve it afterward. In general, while the original technological patterns contributed to the immediate growth of INVs (that is, 1 year after the market entry), the results of this study reveal that the changes that occurred in the patterns have more significance on the post-entry growth (that is, 4 years after the market entry). Therefore, this study is supported by earlier works that emphasize the role of innovation as a stimulus for internal change as well as resource adaptation as a means of achieving sustainable growth in the international markets.
Keywords: M13; F23; 650; Adaptation; Configuration; Innovation; International new ventures; Post-entry growth; Technological patterns